2016
DOI: 10.1007/s10461-016-1496-5
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Antiretroviral Therapy (ART) Adherence in a Sample of Heavy Drinking HIV-Infected Men Who Have Sex with Men (MSM)

Abstract: Cigarette smoking and heavy alcohol use is prevalent among HIV-infected men who sex with men (MSM) and have been linked to imperfect antiretroviral therapy (ART) adherence. Our study examined the correlates of smoking and whether smoking was independently associated with imperfect adherence in heavy-drinking HIV-infected MSM. Of the 185 participants, approximately half (n = 91, 49.2%) reported having smoked cigarettes in the past 30 days. Current smokers were more likely to have reported imperfect adherence co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…While the smoking prevalence was lower than other samples of HIV-positive adults (Cioe et al, 2016; Lifson et al, 2010; O'Cleirigh et al, 2015), these findings are consistent with prior research illustrating that people living with HIV are significantly less likely to quit smoking, despite the availability of pharmacologic and behavioral smoking cessation aids. Prior studies have reported relatively high motivation to quit smoking among people living with HIV and high rates of quit attempts (Benard et al, 2007); however, this readiness may not appear to translate into successful smoking cessation, as demonstrated in this study and others (Mdodo et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…While the smoking prevalence was lower than other samples of HIV-positive adults (Cioe et al, 2016; Lifson et al, 2010; O'Cleirigh et al, 2015), these findings are consistent with prior research illustrating that people living with HIV are significantly less likely to quit smoking, despite the availability of pharmacologic and behavioral smoking cessation aids. Prior studies have reported relatively high motivation to quit smoking among people living with HIV and high rates of quit attempts (Benard et al, 2007); however, this readiness may not appear to translate into successful smoking cessation, as demonstrated in this study and others (Mdodo et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Prior studies have also demonstrated that PWH with alcohol problems also have a higher prevalence of smoking, marijuana and other drug use, and an increased prevalence of psychiatric symptoms, including depression and anxiety. 1,21,3638 A study in the Veteran’s Administration Cohort Study (VACS) indicated that alcohol, smoking and depression synergistically contribute to poor health. 39 Here, we also confirmed co-occurrence of these behavioral risk factors, although moderate/severe depression was only associated with hazardous drinking in bi-variate models.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicate that structural and socioeconomic conditions, as well as psychosocial factors (depression, anxiety), that were associated with smoking behavior are also predictive of suboptimal ART adherence. Prior research indicates that smokers, compared with nonsmokers tended to have multiple and inter-related structural and socioeconomic conditions, as well as psychosocial factors, that were associated with suboptimal ART adherence [ 27 ]. Improved understanding of the ways in which these factors co-occur and affect health-related behaviors may improve the efforts to decrease the burden of tobacco smoking when integrating adherence interventions into clinical settings.…”
Section: Discussionmentioning
confidence: 99%